(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
It is important to study the effect of erosion processes on the agro physical features of the soil in efficient use of dry land, preserving and enhancing fertility, higher yield and high-quality crops, application of different agrotechnology’s. This article describes a change of general physical features of typical gray soils in dry land under the influence of erosion processes.